N-(2-Ethyl-phen-yl)phthalimide. - Fan, Y.M.; Zakaria, N.; Ariffin, A.; Ng, S.W. (International Union of Crystallography, 2008)
In the title compound, C(16)H(13)NO(2), the phthalimide and benzene ring systems form a dihedral angle of 77.2 (1)°.